2016
DOI: 10.1158/1078-0432.ccr-15-1213
|View full text |Cite
|
Sign up to set email alerts
|

Association of Variants in Candidate Genes with Lipid Profiles in Women with Early Breast Cancer on Adjuvant Aromatase Inhibitor Therapy

Abstract: Purpose Aromatase inhibitors (AI) can exert unfavorable effects on lipid profiles; however, previous studies have reported inconsistent results. We describe the association of single-nucleotide polymorphisms (SNP) in candidate genes with lipid profiles in women treated with adjuvant AIs. Experimental Design We conducted a prospective observational study to test the associations between SNPs in candidate genes in estrogen signaling and AI metabolism pathways with fasting lipid profiles during the first three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…NCOA1 encodes a transcriptional coactivator for steroid. It controls energy balance between white and brown adipose tissues [ 30 ]. Both KLHL29 and APOB have been reported as candidate genes for blood lipids [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…NCOA1 encodes a transcriptional coactivator for steroid. It controls energy balance between white and brown adipose tissues [ 30 ]. Both KLHL29 and APOB have been reported as candidate genes for blood lipids [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As directed per protocol, the percentage of women who developed AIMSS over 12 months was compared to historical controls from the Exemestane and Letrozole Pharmacogenetics (ELPh) trial (NCT00263913) who were not taking bisphosphonates. The ELPh trial was a prospective multicenter randomized observational open-label trial in postmenopausal women with early-stage breast cancer (stage 0-III) evaluating the effects of 2 years of therapy with either letrozole or exemestane on a variety of biomarkers of estrogen activity and potential AI toxicity, including a prospective evaluation of AIMSS; these results have been previously published [8, 17]. Participants on the ELPh trial who were randomized to letrozole not taking bisphosphonates at any point during the initial 12 months were included in this analyses as historical controls; those randomized to exemestane or taking bisphosphonates were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Santa-Maria et al [84] have recently reported that several SNPs influence the plasma lipid levels in patients treated with letrozole, where rs4646, rs10046, rs700518, rs749292, rs2289106, rs3759811, and rs4775936 decreased triglyceride levels and had a variable effect on the level of HDL-C.…”
Section: Variations In Cyp19a1 Gene and Breast Cancermentioning
confidence: 99%